An Implementation of Demonstration Using Project-Based Learning to Teach Speaking of Procedure Text - Hardika, Bunga Satya; Bambang Widi Pratolo (English Education Department, 2024)
The study entitled Implementation of Demonstration Using Project-Based Learning to Teach Speaking of Procedure Text at the Broadcasting Class XI of SMK Muhammadiyah Prambanan has been conducted to provide the answer to the research problem. This research is concerned with implementation of the demonstration technique to teach speaking of procedure text to the eleventh graders of SMK Muhammadiyah Prambanan. It tries to answer the questions of (1) how is the implementation of the demonstration technique to teach speaking of procedure text to the Broadcasting Class XI of SMK Muhammadiyah Prambanan, (2) how is the students’ speaking ability after the implementation of the demonstration technique using Project-Based Learning (3) what are the students’ responses toward the implementation of the demonstration technique to teach speaking of procedure text. The subjects of this research were all the 35 students of Broadcasting class XI of SMK Muhammadiyah Prambanan. This study employed descriptive qualitative approaches. The implementation of text procedure demonstrations through project-based learning. Students' speaking ability using demonstration on procedure text with project-based learning approaches has increased in terms of performance and courage. Because it was done in groups, students who were afraid and shy to speak, became motivated and willing to speak. Meanwhile, students' responses to the application of demonstration techniques with a project-based learning were positive. It was seen from the results of observations and questionnaires that the students were happy to learn speaking of procedure text by demonstration. The use of a collaborative project-based learning approach also makes it easier for students.